(3GdebGUO GdTGajI aj TQM GdNdGUI GdcGajI (B( (3CdajI GHf eGdc (B)s - (3GdTGWHj , EHQGgje Hf ehSi Hf eMeO GddNej GdZQfGWj,J (B790 (3g` s
(3ChdgG (B:s
(3jHOC GdehLhO efg HTQM bhd GdfGXe (B:" (3CMeO QHi Gddg NjQ eGdc(B" (3Hbhdg CeG GdMeO aeYfGg GdKfGA Ydi Gddg JYGdi HUaGJ GdceGd hGdEfYGe hGdEaVGd s
(3BNQgG (B:s
(3jfJgi HTQN bhd GdfGXe ef HGH GdaGYd (B: (3hBNQ GdeaYhd Ef dHS MP Q Ch GVeQ GdaGYd ZjQ efMUQ hCNQ eG ajg bhdg (B: (3hef bOQ Ydi GdLhGH CLGH GfJgi GdQHY GdChd ef TQM GdTGWi hGddg CYde s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B75 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B118s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs